Psychological peculiarities of professional development in late adulthood - E. F. Zeer; E. E. Symanyuk; A. A. Ryabukhina; G. I. Borisov (Образование и наука)
Introduction. Modern technologies are generating new types of production and transformation of old ones, which results in the loss of jobs, income and status among the representatives of elder generation and leads to a professional loss crisis. All these factors make it necessary to study the peculiarities of professional development in late adulthood.The aim of the current publication is to investigate psychological peculiarities of professional development in late adulthood.Methodology and research methods. The conceptual idea of the research methodology is the subject-based approach, which considers an individual as an active subject of labour, who is able to successfully and effectively realise various occupational activities, thus ensuring a decent standard of living. A standardised questionnaire “Motivation of Professional Activity” by K. Zamfir in modification of A. A. Rean was used to assess the level of internal and external motivation. The “WHO Quality of Life-BREF (WHOQOL-BREF)” was applied to determine the level of quality of life. The parameters of professional development were evaluated employing a questionnaire with closed-type questions – adapted method “Questionnaire of a Working Pensioner” by N. S. Glukhanyuk and T. B. Sergeeva. The study involved 77 professional respondents aged from 50 to 74 years (19 men and 58 women). The Mann-Whitney U-test, Spearman rank correlation coefficient were used for statistical analysis of the obtained data. Maximum likelihood factor analysis was used as well.Results. The comparison of motivation among the respondents of various age groups demonstrated that the employees over 60 years are more motivated to stability and working conditions than the employees aged 50-60. The comparison of professional experience showed that employees with more than 30 years of working experience rated their physical and mental health and well-being higher than employees with 21-30 years of professional experience. Correlation analysis confirmed the research hypothesis about the correlation between the quality of life and work motivation with the characteristics of professional development. It was also confirmed that the quality of life in late adulthood is associated with the ability to overcome workplace challenges. Factor analysis revealed the factors of psychological preparedness for mentoring (“Need for Mentoring”, “Benefits of Mentoring”, “Impact of Mentoring on the Main Place of Work”, “Cons of mentoring”), the factors of self-assessment of work activity (“Social Aspect”, “Professional Aspect”, “Continuation of Work”, “Demand in the Labour Market”) and the factors of psychological difficulties in late adulthood (“Age Changes”, “Impact of Experience”, “Psychophysiological difficulties”, “Cognitive Changes”). Scientific novelty. For the first time in developmental psychology, the relationship between motivation and quality of life at a later age is discussed; the most significant factors of professional development are analysed. It is established that the most important characteristic of the quality of life for professional development is the environment. The results of the study prove the validity of considering late adulthood as the age of development, which contains the necessary psychological resources to overcome age-related changes and realise oneself in professional activities.Practical significance. The data obtained are important for developing a strategy of professional development in late adulthood, which will allow for determining the methods of the psychological support of employees, the improvement of productivity and the reduction of occupational injuries. Based on the specifics of motivation of professional activity in late adulthood and the characteristics of quality of life, the relevant programmes can be developed to overcome the professional loss crisis.